Success in Failed States:: Canadian Military Strategy in Somalia and the Implications for Afghanistan - Dawson, Grant (Journal of Conflict Studies, 2008)
ABSTRACT This article on the Canadian mission in Somalia takes a contrarian approach to the conventional wisdom, which – focusing on the torture and murder of a Somali civilian – holds that the Canadian effort was a disaster. It points out that in the Somalia operation one can see the genesis of the "3D" (Defence, Development, Diplomacy) approach which now so clearly defines the Canadian mission in Afghanistan. The Canadian Forces first worked to establish security, then encouraged Somalis to embrace the peace-making process. The Canadians 'led from behind,' working with and encouraging local leaders to define community needs and projects. Finally, they engaged other Canadian government agencies to provide the development and reconstruction resources. However, I caution readers about the perils of drawing 'lessons' from the Somalia case, if only because one lesson that could be drawn easily would be to avoid such operations altogether and leave failed states to fester. The article argues that the application of the 3D approach in Afghanistan was simply a case of doing 'what works.' The real lesson of Somalia is that rescuing failed states requires patience – years, even decades, of commitment – and huge amounts of money, talented people, and political will.